Lower creatinine as a marker of malnutrition and lower muscle mass in hemodialysis patients - Yildiz A (Dove Medical Press, 2015)
Abdulmecit Yildiz,1 Fatih Tufan2 1Department of Nephrology, Uludag University School of Medicine, Bursa, 2Department of Geriatrics, Istanbul Faculty of Medicine, Istanbul University, Istanbul, TurkeyWe read the recently published and well-designed study of Lee et al that suggests that bioimpedance analysis (BIA) gives relevant information about hydration status and malnutrition in hemodialysis patients. The authors recommend that utilization of BIA routinely in hemodialysis patients would be rational. We would like to make a few comments about their study.View original paper by Lee et al.